Integrating Semitic Rhetorical Analysis and Scientific Exegesis: A Structural Reading of Surah Al-Thariq - Aqdi Rofiq Asnawi (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2026)
This study investigates the integration of Semitic Rhetorical Analysis (SRA) and scientific exegesis to enhance the interpretation of Surah Al-Thariq (Q. 86). Drawing on Michel Cuypers’ SRA framework, the research explores how the Surah’s rhetorical structure reveals thematic coherence and theological depth, particularly in its engagement with cosmological and natural phenomena. Focusing on key verses—such as verse 3 (the piercing star), verses 6–7 (human creation), verse 11 (atmospheric layers), and verse 12 (geological foundations)—the analysis demonstrates how SRA contextualizes scientific interpretations within the Surah’s parallel structure. Analyses of scientific insights, including pulsars, embryological development, atmospheric regulation, and tectonic dynamics, reveal a significant consonance with Qur’anic descriptions, suggesting a close correspondence between scripture and modern scientific perspectives. SRA enriches this alignment by framing these phenomena as rhetorical devices that support the Surah’s central eschatological themes—resurrection, divine omnipotence, and cosmic order. The synthesis of SRA and scientific exegesis thus bridges revelation with modern knowledge, affirming the Qur’an’s layered communicative strategy and its enduring capacity to convey spiritual and intellectual meaning.